Synthesis of bipyramidal gold nanoparticle-[C60]fullerene nanowhisker composites and catalytic reduction of 4-nitrophenol. Issue 12 (2nd December 2017) - Ko, Jeong Won; Ko, Weon Bae
ABSTRACT: The seed solution was prepared by dissolving hydrogen tetrachloroaurate(III) trihydrate (HAuCl4 ·3H2 O), trisodium citrate dihydrate (C6 H5 Na3 O7 ·2H2 O), and sodium borohydride (NaBH4 ) in distilled water. The resulting reddish-purple seed solution was stirred for 3 h at room temperature. The growth solution was prepared by mixing hydrogen tetrachloroaurate(III) trihydrate (HAuCl4 ·3H2 O), cetyltrimethylammonium bromide (CTAB, (C16 H33 )N(CH3 )3 Br), silver nitrate (AgNO3 ), hydrochloric acid (HCl), and ascorbic acid (C6 H8 O6 ) in distilled water. Subsequently, 100 μL of this seed solution was transferred into 10 mL of the growth solution. The mixed solution was maintained at 30 °C for 3 h to obtain a solution of bipyramidal gold nanoparticles. The bipyramidal gold nanoparticle-[C60 ] fullerene nanowhisker composites were synthesized by applying the liquid-liquid interfacial precipitation (LLIP) method to a saturated solution of C60 in toluene, the solution of bipyramidal gold nanoparticles, and isopropyl alcohol. The prepared bipyramidal gold nanoparticle-[C60 ] fullerene nanowhisker composites were characterized by X-ray diffraction, Raman spectroscopy, scanning electron microscopy, and transmission electron microscopy. The catalytic activity of these composites was confirmed in the reduction of 4-nitrophenol by UV-Vis spectroscopy.